1999
DOI: 10.1897/1551-5028(1999)018<1270:coetpi>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Explosives Transformation Products in Plant Tissue

Abstract: Explosives contamination in surface or groundwater used for the irrigation of food crops and phytoremediation of explosives-contaminated soil or water using plant-assisted biodegradation have brought about concerns as to the fate of explosives in plants. Liquid scintillation counting, high-performance liquid chromatography, and gel permeation chromatography were utilized to characterize explosives (hexahydro-1,3,5-trinitro-1,3,5-triazine and trinitrotoluene) and their metabolites in plant tissues obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…[24][25][26][27] Among solvents used to extract explosives in plants, methanol, acetonitrile and acetone are often selected. [18,[28][29][30][31] However, methanol, acetonitrile, and their mixtures with water are applied in our test since acetonitrile is the solvent used in EPA Method 8330, which is the standard method for the determination of nitroaromatics and nitramines in water, soil, and sediment by HPLC being modified to apply in several studies to extract explosives in plant tissues [21,[32][33][34] , whereas methanol was reported to be a better solvent than acetonitrile and acetone to extract RDX, HMX, TNT and their metabolites from plant tissue with LC/MS. [19] Understanding optimal solvent selection will aid future research in potential food chain studies or in phytoremediation and phytoforensic for various explosives present simultaneously in plant tissue using LC-MS/MS and other analytic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Among solvents used to extract explosives in plants, methanol, acetonitrile and acetone are often selected. [18,[28][29][30][31] However, methanol, acetonitrile, and their mixtures with water are applied in our test since acetonitrile is the solvent used in EPA Method 8330, which is the standard method for the determination of nitroaromatics and nitramines in water, soil, and sediment by HPLC being modified to apply in several studies to extract explosives in plant tissues [21,[32][33][34] , whereas methanol was reported to be a better solvent than acetonitrile and acetone to extract RDX, HMX, TNT and their metabolites from plant tissue with LC/MS. [19] Understanding optimal solvent selection will aid future research in potential food chain studies or in phytoremediation and phytoforensic for various explosives present simultaneously in plant tissue using LC-MS/MS and other analytic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that RDX is rapidly assimilated by the roots of higher plants (trees) and by fodder and crop plants from soils (Cataldo et al 1990;Fellows et al 1995;Checkai and Simini 1998;Checkai et al 1996;Price et al 1997;Larson et al 1999;Lachance et al 2003;Fellows et al 2006). Results from these studies demonstrate that RDX is readily absorbed by plants from both soil and irrigated water and those plants grown in RDX-contaminated soil bioaccumulated RDX, with plant concentrations being greater than soil concentrations.…”
Section: Measurements Of Rdx In the Environmentmentioning
confidence: 98%
“…The biodegradation of nitroaromatic compounds (NACs) was performed by microbial cells (Nishino et al 1993, Boopathy et al 1994, Scheibner et al 1997, Samson et al 1998, by lower plants (Tadros et al 2000), as well as by higher plants (Larson et al 1999, Bhadra et al 1999a,b, Vaněk et al 2003, Snellix et al 2001. Only a few papers were focused on the study of enzyme(s) participating in the degradation of nitroaromatics (Mishkiniene et al 1998) and tests of nitroreductase activity Spain 1996, Shah andCampbell 1997).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Only a few papers were focused on the study of enzyme(s) participating in the degradation of nitroaromatics (Mishkiniene et al 1998) and tests of nitroreductase activity Spain 1996, Shah andCampbell 1997). The TNT degradation pathway in plants is based on reduction of TNT nitrogroups (Vanderford et al 1997, Rivera et al 1998, Larson et al 1999, Vaněk et al 2003, Nepovím et al 2004. The reaction leads to formation of aminodinitrotoluenes (Fig.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%